Introduction to the Special Issue on Statistical Language Modeling - Gao, Jianfeng; Lin, Chin-Yew (ACM Transactions on Asian Language Information Processing, 2004)
The goal of statistical language modeling (SLM) is to estimate the likelihood (or probability) of a word string. SLM is fundamental to many natural language applications like automatic speech recognition (ASR) [Jelinek 1990], statistical machine translation (SMT) [Brown et al. 1993], and Asian language text input [Gao et al. 2002a]